CSC585: Introduction to Hybrid Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
This fundamentals programming subject teaches to computer science, applied science and engineering students. This subject covers the problem-solving methods, algorithm development and data structures using different programming approach or hybrid programming such as Structured and Object-oriented.